How the COVID-19 pandemic and related school closures reduce physical activity among children and adolescents in the WHO European Region: a systematic review and meta-analysis - Ludwig-Walz, Helena; Siemens, Waldemar; Heinisch, Sarah; Dannheim, Indra; Loss, Julika; Bujard, Martin (International journal of behavioral nutrition and physical activity, 2023)
Emerging research suggests that physical activity among children and adolescents decreased during the COVID-19 pandemic. However, a differentiated overview of European youth is lacking. In particular, no systematic analysis has been conducted to date on the impact of heterogeneous pandemic restrictions and school closures within European countries, and with regard to potentially vulnerable groups.